Spontaneous vocalizations and communicative identity - Jederlund, Ulf (Socialmedicinsk tidskrift, 2022)
The purpose of the article is to draw adults’ attention to children’s spontaneous vocalizations and spontaneous singing and its importance for children’s relational, communicative and social development. The text emphasizes children’s (and everyone’s) innate singing ability and inherent inclination to communicate musically with body and voice. By affirming children’s (and others’) own musical and linguistic expressiveness, we can in both a simple and powerful way strengthen children’s (and others’) communicative identity.